Flow control with rotating cylinders. (21st July 2017) - Schulmeister, James C.; Dahl, J. M.; Weymouth, G. D.; Triantafyllou, M. S.
Abstract : We study the use of small counter-rotating cylinders to control the streaming flow past a larger main cylinder for drag reduction. In a water tunnel experiment at a Reynolds number of 47 000 with a three-dimensional and turbulent wake, particle image velocimetry (PIV) measurements show that rotating cylinders narrow the mean wake and shorten the recirculation length. The drag of the main cylinder was measured to reduce by up to 45 %. To examine the physical mechanism of the flow control in detail, a series of two-dimensional numerical simulations at a Reynolds number equal to 500 were conducted. These simulations investigated a range of control cylinder diameters in addition to rotation rates and gaps to the main cylinder. Effectively controlled simulated flows present a streamline that separates from the main cylinder, passes around the control cylinder, and reattaches to the main cylinder at a higher pressure. The computed pressure recovery from the separation to reattachment points collapses with respect to a new scaling, which indicates that the control mechanism is viscous.